INNOVATIVENESS SURVEY ON MANUFACTURING COMPANIES IN TASIKMALAYA CITY - Edy Suroso; Ina Primiana (Journal of Management and Business, 2014)
Innovation is one of most important sources of competitive advantage. The purpose of this paper is to analyze innovativeness by using the 55 operations managers of manufacturing companies in Tasikmalaya City as respondents. The results showed the four types of clusters of Innovativeness consisting of (1) Leading Innovator that have the out class value than the others in every aspects of innovativeness, (2) Followers cluster is as the very low radical product innovations capability, (3) Inventors are very strong in radical product innovations, while (4) Lagers are at the lowest scores in all innovation types among the clusters. Based on ANOVA, it is concluded that every group of innovation type has its own success difference. The leading innovators type has the highest mean of business success measured by the comparison innovations type among groups in the growth of sales.